Construction of 2, 6, 9, 11-tetraoxatricyclo[6.2.1.03, 8]undecane containing 4-keto-d-glucose skeleton. Issue 51 (21st December 2017) - Fujitani, Ban; Hanaya, Kengo; Higashibayashi, Shuhei; Shoji, Mitsuru; Sugai, Takeshi
Abstract: A unique tricyclic bisacetal, 2, 6, 9, 11-tetraoxatricyclo[6.2.1.0 3, 8 ]undecane observed in cotylenin A, was constructed in a simplified model compound, based on 6- O -methyl-4-keto-d -glucose as the scaffold to control of the stereochemistry. The key compound was an unprecedented spirolactone formed from the α-(α′-hydroxy)acyloxy dimethyl acetal, accompanied with stereoselective migration of an acyl group. Subsequent intramolecular acetalization between the hydroxy group at the C-3 and the C-1′ hemiacetal position furnished the desired tricyclic bisacetal. Graphical abstract: